An 8-week-old infant with trisomy 13: dilemmas for medical decision making - Staso, Patrick; Paitl, Scottie; Patel, Dilip R. (AME Case Reports; Vol 2 (January 2018): AME Case Reports, 2018)
Patau syndrome, trisomy 13, is a rare genetic condition with notable physical and mental characteristics and an average reported lifespan of 9 months. For years, trisomy 13 was regarded as a lethal condition; however, a few infants survive for many years, creating a dilemma for both the medical practitioner and the family in terms of the appropriateness and timeliness of specific medical interventions. Even in the face of severe mental and physical limitations, most families of children with trisomy 13 report their experiences as enriching. Appropriate and timely surgical interventions and medical treatments have been shown to increase survival for some infants. Early palliative care helps to limit physical and emotional suffering, and allow the family to create a legacy that their baby’s life had meaning, regardless of how long they survive. We present a case of an 8-week-old infant with trisomy 13 to illustrate some of the medical decision making dilemmas faced by both medical practitioner and the family.